Pembelajaran dan Pengenalan Musik dalam Melatih Daya Ingat Anak - Fathan Mubina Dewadi (JECED : Journal of Early Childhood Education and Development, 2021)
Learning through songs can be related to kinesthetic and physical abilities because when someone listens to a song/music, the sensory nervous system works and transfers it to the motor nerves. This research is included in field research. The approach used is a descriptive qualitative approach, which is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior, with data sources consisting of primary data and secondary data. Primary data is data obtained from interviews with the child and with the parents. For secondary data obtained by looking at the literature related to this journal. On average, children who have difficulty focusing, namely because the child lacks adequate rest, does not sleep enough, does not eat breakfast, does not understand the subject matter, has understood the lesson and does not feel challenged, lacks motivation from teachers and parents, is disturbed by the surrounding environment and does not match the given learning style. Playing sounds that can help children learn to make children learn as if they are playing.